MEDIA PEMBELAJARAN MENULIS SUBMATERI EYD DENGAN MACROMEDIA AUTHORWARE 7.0 UNTUK SISWA KELAS XI SMA/MA - Farida, Septiana (Pelita - Jurnal Penelitian Mahasiswa UNY, 2015)
This research is conducted to develop a computer assisted learning media to teach writing sub"material EYD (Ejaan Yang Disempurnakan) by using Macromedia Authorware 7.0 and to find out the quality of the media in the form of CD so that it is applicable as an alternative learning. The research was carried out by referring to Borg and Gail, but in its progress it was simplified into six steps which are (1) Doing need analysis, (2) Developing the product, (3) Validating the program by the user and expert judgment, (4) Revising the product, (5) Testing the product using two pre"tests and post"tests, (6) Revising the final product. The subjects were the second semester students of XI IPS 3 MAN Yogyakarta III. The data were obtained from the questionnaires with a 1"4 scale rating converted according to the assessment criteria. The data also came with a limited trial result through the pre"test and post"test by students. The results ofthe product validation by two experts ofmaterial and media showed the scores with the criteria ofprofoundly agree. Phase I of the user validation produced a mean score in the criteria of profoundly agree. The second phase of validation produced a mean score in the criteria of profoundly agree in terms of the appearance and learning aspects, and the mean score with the agree criteria in terms of the content / learning aspects. The results ofthe pre"test and post"test in the both phases showed an increasing average score by 10% for the first phase and 10.875% for the second phase. Keywords : learning media, writing, EYD